2019
DOI: 10.1038/s41586-019-1170-y
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells regulate tumour ferroptosis during cancer immunotherapy

Abstract: Summary Cancer immunotherapy restores and/or enhances effector function of CD8+ T cells in the tumor microenvironment1,2. CD8+ T cells activated by cancer immunotherapy execute tumor clearance mainly by inducing cell death through perforin-granzyme- and Fas/Fas ligand-pathways3,4. Ferroptosis is a form of cell death that differs from apoptosis and results from iron-dependent lipid peroxide accumulation5,6. Although it was mechanistically illuminated in vitro7,8, emerging evidence has shown that ferroptosis may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
1,630
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,942 publications
(1,776 citation statements)
references
References 30 publications
30
1,630
1
1
Order By: Relevance
“…Other Molecular Indicators : In addition to the molecules discussed above, ferroptosis process can also be monitored by detection of GSH depletion, release of glutamate, and cystine uptake . Proteins involved in ferroptosis, such as SLC7A11 can be characterized by immunofluorescence staining .…”
Section: Basis Of Ferroptosismentioning
confidence: 99%
See 2 more Smart Citations
“…Other Molecular Indicators : In addition to the molecules discussed above, ferroptosis process can also be monitored by detection of GSH depletion, release of glutamate, and cystine uptake . Proteins involved in ferroptosis, such as SLC7A11 can be characterized by immunofluorescence staining .…”
Section: Basis Of Ferroptosismentioning
confidence: 99%
“…In addition to the combination of multiple forms of RCDs for eradicating malignancies, the non‐apoptotic nature of ferroptosis also inspired research on the immunostimulatory property of ferroptosis inducers . One of the pioneer work described a biomimetic magnetosome nanoparticle (Pa‐M/Ti‐NCs) for ferroptosis/immunomodulation synergistic cancer therapy ( Figure ).…”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed recurrent dysregulation of ferritin and HSP90-related genes, suggestive of an enhanced acute-phase protein reaction, iron loading and molecular stress in the context of chromosome 7 gain and immunotherapy failure. Iron availability is known to influence tumor cell survival and the function of numerous immune cell types including T cells; however, these competing outcomes have been poorly studied in solid tumors such as melanoma 39,40 . Nevertheless, a potential role for immunosuppressive neutrophil phenotypes and iron trafficking within the TME warrants further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al reported that CD8+ T cells could promote tumor ferroptosis during cancer immunotherapy treatment (Wang et al, 2019). Thus, ferroptosis might play important roles during cancer progression and treatment, and a systematic study for ferroptosis and its aberrances across cancers will be helpful.…”
Section: Introductionmentioning
confidence: 99%